Caballeros de la oscuridad: la Orden del Temple en el cine de Amando de Ossorio - Huertas Morales, Antonio; Bosch Moreno, María (Romanica Silesiana)
The tragic end of the Templars turned them into a myth that has left a deep mark on the contemporary narrative. Currently, seen as innocent martyrs, the Templars acquired features, as wanted San Bernardo, of celestial militia, fighting the forces of evil. However, the legends that bind tight and unorthodox beliefs have shifted even historiographical versions, and the Templars also become dark and intriguing characters. Before the massive appearance of the Templars in Spanish narrative of the end of the millennium, the Galician filmmaker Amando de Ossorio made some films about the warriors-monks, giving them horror film features and binding them to the family of vampires, mummies and zombies. The treatment they were given by the Galician filmmaker, despite the originality and some of the literary reminiscences, is to be inserted in the continuous process of mystification of the Templars. Key words: Order of the Temple, mythology, Amando de Ossorio, cinema, medieval-themed narrative<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />